OPTIMASI PERFORMANSI AJAX DENGAN MENGGUNAKAN JSON - Yanuar Firdaus Arie Wibowo; Dana Sulistiyo Kusumo; Annas Abdillah Marta (Seminar Nasional Informatika (SEMNASIF), 2008)
Web-based application development at this time concentrate or on the way to interactivity and response time closely to desktop application. AJAX (Asynchronous JavaScript and XML) is one of  method to create a web-based application become more interactive like desktop application, with AJAX is possible for web not to reload full of one web page again from server but only part of information on page that requested, with the result is improvement of bandwidth usage.AJAX web application in connection with web server usually use XML (Extensible Markup Language) as data interchange format, but XML have redundancy in their data format, it have duplicated at tags (opening and closing tags) that cause less efficient and probably impact to AJAX performance. JSON (JavaScript Object Notation) is alternative data interchange format can be used in AJAX that has less redundancy than XML, it make JSON more lightly better than XML. Web performance it can be know from response time and bandwidth.Test result is showing that for large amount of data, AJAX performance with JSON is better than AJAX with XML but there are little different result from attribute that used in XML, test result for user access is showing same pattern with testing in single computer.